Exploratory two-level analysis of individual- and school-level factors on truant youth emotional/psychological functioning. Issue 6 (1st November 2016) - Dembo, Richard; Wareham, Jennifer; Schmeidler, James; Winters, Ken C.
ABSTRACT: Research on samples of truant adolescents is limited, with little known about mental health problems among truant youths. This study provided an exploratory, multilevel examination of mental health problems for a sample of 300 truant adolescents. Confirmatory factor analysis indicated a single factor of multiple mental health problems at the individual level, but the structure of these problems was not the same at the school level. A number of covariate effects were found at the individual level on the mental health factor. Further, youths attending middle school were more likely to report attention deficit hyperactivity disorder (ADHD) problems than those in high school. Service and practice implications of better understanding school and mental health issues of truant youth are discussed.